BL-algebras with pseudo MV-valuations - Yang, Yongwei; Wang, Yongzhao; Wang, Qiaoling (IJRDO -JOURNAL OF MATHEMATICS, 2018)
The concept of pseudo MV-valuations on BL-algebras is introduced, which provides a new idea for the study of BL-algebras from MV-algebras. Some relatedcharacterizations of pseudo MV-valuations and conditions for a function to be a pseudo MV-valuation are provided. The notion of pseudo MV-metric spaces is alsogiven, and properties of pseudo MV-metric spaces are given by discussing pseudo MV-metrics induced by pseudo MV-valuations.